Benefit Entitlement and Unemployment Duration: The Role of Policy Endogeneity - Rafael Lalive; Josef Zweimüller (Institute for the Study of Labor (IZA), 2002)
The potential duration of benefits is generally viewed as an important determinant of unemployment duration. This paper evaluates a unique policy change that prolonged entitlement to regular unemployment benefits from 30 weeks to a maximum of 209 weeks for elderly individuals in certain regions of Austria. In the evaluation, we explicitly account for the fact that the program was an endogenous policy response to a crisis affecting individuals with severe labor market problems. The main results are: (i) REBP reduced the transition rate to jobs by 17 %; (ii) accounting for endogenous policy adoption is important and quantitatively significant.
Keywords: J65; J64; C41; 330; quasi-experiments; policy endogeneity; benefit entitlement; maximum benefit duration; unemployment duration; unemployment insurance; Arbeitslosigkeit; Dauer; Arbeitslosenversicherung; Österreich